Essentials of Clinical Mycology - Kauffman, Carol A.; Pappas, Peter G.; Sobel, Jack D.; Dismukes, William E.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Essentials of Clinical Mycology gives a comprehensive overview of the field of clinical mycology. It is written for clinicians who care for patients who have fungal infections. Each of the major systemic fungal infections is discussed in regard to mycology, pathogenesis, epidemiology, clinical manifestations, diagnosis, and treatment. The increasing antifungal armamentarium is described in depth, and separate chapters review increasing antifungal resistance and the use of combination therapy. A section is devoted to high-risk patients who have received a stem cell or solid organ transplant, are neutropenic, or have HIV infection and who are at high risk for developing invasive fungal infections.
PART I INTRODUCTION -- Laboratory Aspects of Medical Mycology -- Epidemiology of Systemic Fungal Diseases: Overview -- PART II SYSTEMIC ANTIFUNGAL DRUGS -- Amphotericin B -- Liposomal Nystatin -- Flucytosine -- Azole Antifungal Drugs -- Cell Wall Synthesis Inhibitors: Echinocandins and Nikkomycins -- Terbinafine -- Resistance to Antifungal Drugs -- Adjunctive Antifungal Therapy -- PART III MYCOSES CAUSED BY YEASTS -- Candidiasis -- Cryptococcosis -- Rhodotorula, Malassezia, Trichosporon, and Other Yeast-Like Fungi -- PART IV MYCOSES CAUSED BY MOULDS -- Aspergillosis -- Zygomycoses -- Hyalohyphomycoses (other than Aspergillosis and Penicilliosis) -- Phaeohyphomycoses -- PART V MYCOSES CAUSED BY DIMORPHIC FUNGI -- Histoplasmosis -- Blastomycosis -- Coccidioidomycosis -- Paracoccidioidomycosis -- Sporotrichosis -- Penicilliosis -- PART VI MYCOLOGY INVOLVING SKIN AND SUBCUTANEOUS TISSUES -- Superficial Cutaneous Fungal Infections -- Eumycetoma -- Chromoblastomycosis -- PART VII OTHER MYCOSES -- Pneumocystosis -- Miscellaneous Fungi -- PART VIII SPECIAL PATIENT POPULATIONS -- Fungal Infections in Neutropenic Patients -- Fungal Infections in Blood and Marrow Transplant Recipients -- Fungal Infections in Solid Organ Transplant Recipients -- Fungal Infections among Patients with AIDS.
Keywords: Medicine; Immunology; Microbiology; Emerging infectious diseases; Biomedicine; Immunology; Medical Microbiology; Molecular Medicine; Infectious Diseases